Hydrogen embrittlement controlled by reaction of dislocation with grain boundary in alpha-iron. (January 2019) - Wan, Liang; Geng, Wen Tong; Ishii, Akio; Du, Jun-Ping; Mei, Qingsong; Ishikawa, Nobuyuki; Kimizuka, Hajime; Ogata, Shigenobu
Abstract: Hydrogen atoms absorbed by metals in hydrogen-containing environments can lead to the premature fracture of the metal components used in load-bearing conditions. Since metals used in practice are mostly polycrystalline, grain boundaries (GBs) can play an important role in hydrogen embrittlement of metals. Here we show that the reaction of GBs with lattice dislocations is a key component in hydrogen embrittlement mechanism for polycrystalline metals. We use atomistic modeling methods to investigate the mechanical response of GBs in alpha-iron with various hydrogen concentrations. Analysis indicates that dislocations impingement and emission on the GB can provoke it to locally transform into an activated state with a more disordered atomistic structure, and introduce a local stress concentration. The activation of the GB segregated with hydrogen atoms can greatly facilitate decohesion of the GB. We propose a hydrogen embrittlement model that can give better explanation of many experimental observations. Graphical abstract: Highlights: A new hydrogen embrittlement model is proposed for polycrystalline metals. Dislocation - grain boundary reaction is a key process in hydrogen embrittlement. Dislocation - grain boundary reaction causes local activation of grain boundary. Activation of grain boundary segregated with H atoms greatly aids decohesion.